FACTORS CONTRIBUTING TO DRUG ABUSE AMONG YOUTHS OF NAKASEKE TOWN COUNCIL, NAKASEKE DISTRICT, A CROSS-SECTIONAL SURVEY. - SSEMPIJJA, BRANDO; Atukuuma , Cliffe (Student’s Journal of Health Research Africa, 2024)
Background (WHO, 2017) defines drug abuse as the harmful or hazardous use of psychoactive substances including alcohol and illicit drugs. It eventually leads to dependence, a cluster of behavioral, cognitive, and physiological phenomena after repeated substance use despite the harmful consequences. Objectives The study aimed to determine how peer group formation among youths, parental supervision, and drug control laws and policies contribute to drug abuse among youths in Nakaseke town council. Research methods The researcher used a descriptive cross-sectional study design. The targeted population was the youths in Nakaseke town council. The sample size was 100 determined by Kish and Leslie’s method. Data was collected using questionnaires and interviews. Results It was revealed that the majority of respondents have peer groups, while 38% of the respondents misuse drugs. Alcohol is the most abused drug followed by Tobacco, marijuana, and others (which included codeine, morphine, tramadol, & NSAIDs). The study findings showed that most people misuse drugs due to peer pressure 34%, depression 21.1%, media influence 18.4%, curiosity 10.5%, and others (such as excitement, passing time, etc.). Many of the respondents knew individuals counseled for getting involved with drugs, 30% knew those who were imprisoned, 22% were not aware of any punishment given to the victims of drug abuse, and 10% of the respondents mentioned that some would undergo mob justice when they are caught. Conclusion The study concluded that in contrast to peer group formation among youths and drug control laws and policies, parental supervision does not have a significant impact on drug abuse. Recommendations Youth-based & non-governmental organizations, county & national governments, as well as other relevant stakeholders, should devote maximum attention and resources towards factors against drug abuse effectively. Town council-level strategies also influence the relationship of the other factors with drug abuse.